Le tourisme dans la région métropolitaine de Montréal - Proulx, Pierre-Paul; Beaudry, Richard (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractThis article presents summarily the tourist resources and equipment available; the mechanism through which tourists are informed and received; data on the number of tourists (with a forecast) having come to Montreal and the Province of Quebec; information of congress, Expo, the Olympic Games; the expenditures of tourists; the employment and income creation attributable to tourism. It concludes with suggestions to the effect that a multidimensional inter-departmental approach be taken to deal adequately with tourism.